Good Governance-Based Governance in School Infrastructure to Support School Quality - Yudha, Gesit; Mubah, Hilmi Qosim; Mohamoud, Mohamed Esse (Thawalib: Jurnal Kependidikan Islam, 2026)
This study is motivated by the gap between the ideal concept of good governance and the practice of managing school infrastructure, which remains limited in terms of participation, transparency, accountability, and the effectiveness of its implementation at the secondary school level. This research aims to analyze the application of good governance principles in the management of school infrastructure to improve educational quality. The methodology used is a qualitative case study design at Sekolah Menengah Atas Negeri 1 Terusan Nyunyai, employing interview, observation, and documentation techniques, along with data analysis that includes condensation, presentation, and conclusion drawing. The results of the study indicate that infrastructure management has been carried out in a participatory manner by involving all stakeholders in planning and evaluation, is transparent through the disclosure of budget information and the use of digital technologies such as ARKAS, and is accountable through a systematic, well-documented reporting system. In addition, school independence is reflected in its ability to make decisions based on internal needs without external intervention, and in accountability conducted in accordance with applicable regulations. The implementation of these principles has been proven to improve the effectiveness of facilities and infrastructure management and to support the continuous improvement of educational service quality. Thus, the application of good governance in school infrastructure management effectively increases efficiency, transparency, and educational quality. This study is significant as a practical model of good governance-based infrastructure management that can serve as a reference for other schools in improving educational quality.